1987
DOI: 10.1095/biolreprod37.3.699
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Prolactin and Testosterone in the Development and Function of Granulosa Lutein Tissue in the Rat1

Abstract: The luteotropic roles of prolactin and testosterone (or estradiol formed in luteal tissue) were investigated in hypophysectomized rats with homografts of granulosa lutein tissue. Using this approach, we could determine the effects of prolactin independently of estrogen, since granulosa lutein tissue does not produce estrogen de novo under these conditions. Luteinizing granulosa cells were expressed from the ovaries of immature pregnant mare's serum gonadotropin-primed Fischer 344 rats 6 h after injection of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This luteotrophin maintains LH receptor numbers and the capacity of luteal cells to secrete estradiol. Prolactin (or prolactin-like compounds) is sufficient to maintain luteal function for 10 days after ovulation; however, later increases in luteal weight and progesterone secretion require both prolactin and intraluteal estradiol [56,131]. Thus, pregnancy-associated increases in luteal function in the rat are due to a synergistic action of prolactin-like luteotrophins and estradiol.…”
Section: Early Pregnancymentioning
confidence: 99%
“…This luteotrophin maintains LH receptor numbers and the capacity of luteal cells to secrete estradiol. Prolactin (or prolactin-like compounds) is sufficient to maintain luteal function for 10 days after ovulation; however, later increases in luteal weight and progesterone secretion require both prolactin and intraluteal estradiol [56,131]. Thus, pregnancy-associated increases in luteal function in the rat are due to a synergistic action of prolactin-like luteotrophins and estradiol.…”
Section: Early Pregnancymentioning
confidence: 99%
“…Activation of PKC Isoforms by PRL-During the second half of pregnancy, when we detect activated PKC ␦, the rat corpus luteum is maintained exclusively by the combined actions of intraluteal E 2 , aromatized from androgens provided by the placenta (1), and PRL-like hormones such as the placentaderived rPL-1 (1,20). We have found that rPL-1 treatment of luteinized granulosa cells promotes phosphorylation of Stat 3 on tyrosine 705 and serine 727 and induction of relaxin mRNA expression, 2 a major product of the rat corpus luteum in the second half of pregnancy (21).…”
Section: Pkc ␦ Autophosphorylation On Serine 662 Increases In Corporamentioning
confidence: 91%
“…The ␦ isoform can be distinguished from the other isoforms by the striking increase of both PKC ␦ mRNA and protein levels in corpora lutea in the second half of pregnancy (19). The rat corpus luteum is maintained in the second half of pregnancy by the combined actions of intraluteal E 2 and PRL-like hormones such as the placenta-derived rPL-1 (1,20). We have found that rPL-1 treatment of luteinized granulosa cells induces phosphorylation of Stat 3 on both tyrosine 705 and serine 727 and induction of relaxin mRNA expression, 2 a major product of the rat corpus luteum in the second half of pregnancy (21).…”
mentioning
confidence: 99%